PENGEMBANGAN LKPD BERBASIS AUGMENTED REALITY SEBAGAI MEDIA PEMBELAJARAN IPAS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS KELAS IV SEKOLAH DASAR - Kurnia Sari, Gisela; Fathurrahman, Moh. (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is based on the importance of technology-based learning media innovation in the 21st Century era which can improve students' critical thinking abilities. This research aims to develop Student Worksheets (LKPD) as a science learning medium based on Augmented Reality material on the Heritage of Hindu, Buddhist and Islamic Kingdoms in Indonesia for fourth grade elementary school students. In its implementation, this research uses a Research and Development approach by referring to the steps of the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research results show that Augmented Reality-based LKPD material on the Heritage of Hindu, Buddhist and Islamic Kingdoms in Indonesia has "very decent" quality based on the average media and material validation results of 95.32%. The results of teacher and student responses also showed a good assessment with a score obtained of 83%. The product trial results show that the N-Gain calculation results show that the average value for small-scale trials is 0.3674 and the average value for large-scale trials is 0.3293, both of which are included in the "medium" criteria. This shows that the use of Augmented Reality-based LKPD can help students understand the material, is effective, and is suitable for use as a supporting tool for honing critical thinking skills.